2017
DOI: 10.1080/00480169.2017.1344587
|View full text |Cite|
|
Sign up to set email alerts
|

Farm and cow-level prevalence of bovine digital dermatitis on dairy farms in Taranaki, New Zealand

Abstract: Although the prevalence at the cow level was low, if these data are representative of other regions of New Zealand, BDD could easily become a major problem on dairy farms in New Zealand, as has been observed in other countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 20 publications
0
10
1
Order By: Relevance
“…Advanced lesions are very rare in New Zealand. So far, out of 1353 DD affected cows detected by the first author over the years, four "advanced lesions" including the one found in this study have been observed [11,20]. The other three which are morphologically similar to the advanced lesion found in this study were only observed once in cross-sectional studies and no further observations were made on those three.…”
Section: Discussioncontrasting
confidence: 48%
See 1 more Smart Citation
“…Advanced lesions are very rare in New Zealand. So far, out of 1353 DD affected cows detected by the first author over the years, four "advanced lesions" including the one found in this study have been observed [11,20]. The other three which are morphologically similar to the advanced lesion found in this study were only observed once in cross-sectional studies and no further observations were made on those three.…”
Section: Discussioncontrasting
confidence: 48%
“…In pasture-based systems, such as those that predominate in New Zealand, DD lesions are typically less commonly seen than in housed cattle [11]. Furthermore, clinical lameness was rarely associated with DD under New Zealand conditions [12], it is therefore likely that DD will have only limited impacts on herd-level production [13].…”
Section: Introductionmentioning
confidence: 99%
“…These results are similar to a study in the south‐eastern USA with a comparable study design, which found a prevalence of 29% in dairy cattle and 4% in beef cattle. Another recent investigation into DD among dairy cattle has been performed in New Zealand, a pasture‐based dairy industry, with similar conditions to those in south‐east Australia. This research concluded that 63.8% of 224 farms were affected with DD, although the prevalence at a cow‐level was quite low (1.2%).…”
Section: Discussionmentioning
confidence: 99%
“…Bovine digital dermatitis (BDD) has been found throughout the world in both confined and pasture-based dairy systems [1, 2]. In many countries, BDD appears to be endemic in dairy herds [3] and is commonly considered as the most important infectious cause of cattle lameness [4].…”
Section: Introductionmentioning
confidence: 99%